Sosialisasi Strategi Manajemen SDM dalam Upaya Meningkatkan Kualitas Produk Makanan Olahan di UMKM Desa Margaluyu - Sarusu, Armansyah M.; Suherman, Jajang; Akmaliah, Miflahul; Oktafiansyah, Okky (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2024)
Margaluyu Village, located in Bandung Regency, is known for processed lemon and tomato products produced by local Micro, Small, and Medium Enterprises (MSMEs). Although these products have good potential, MSMEs in this village face various challenges that hinder their competitiveness, especially related to the lack of product diversification and limited human resource (HR) management. This condition affects the quality of products and production processes, which ultimately has an impact on competitiveness in the market. This activity method uses PAR (ParticipacyAction Research) involving MSME actors in Margaluyu Village. Results of the activity show that MSME actors are able to produce processed lemon and tomato products with better quality, both in terms of taste, packaging, and product durability, product diversification, increased product efficiency and are able to compete better in the local market and even open up wider market opportunities thanks to the implementation of more effective marketing strategies.